Improvement by Medication Less than Expected in Parkinson’s Disease: Blinded Evaluation of Levodopa Response - Mette Niemann Johansen; Anna Handberg; Mohamed El Haddouchi; Josefine Grundtvig; Steen Rusborg Jensen; Lisette Salvesen; Annemette Løkkegaard (Parkinson's Disease)
Background. The latest Movement Disorder Society (MDS) diagnostic criteria require a good and sustained response to medication to get a diagnosis of Parkinson’s disease, PD. Objective. The aim of this study was to evaluate levodopa response in a group of patients with probable PD, diagnosed by movement disorder specialists. Methods. An acute levodopa challenge test (LDCT) was performed after pausing the dopaminergic medication for 6 half-times. The motor part of the Unified Parkinson’s Disease Rating Scale was performed in the OFF-state and after LDCT (ON). A good effect was defined as >30% improvement. A video-protocol was used to secure standardized motor examination with blinded assessments of the UPDRS-III OFF and ON. An age-matched group of control subjects (CS) was included but did not go through LDCT. All participants were evaluated with Montreal Cognitive Assessment (MoCA) and Beck’s Depression Inventory (BDI). Results. In the statistical analysis, 37 patients were included. Twenty-one patients showed an improvement ≤30%, while 16 patients showed an improvement >30%. LDCT showed an overall mean improvement of 27.3% of motor UPDRS. In 43.2%, there was a discrepancy between the effect seen with the LDCT and the patients’ self-perceived medicine evaluation. Patients with PD had a significantly lower MoCA score and more depressive symptoms compared to CS. Conclusions. We showed an acute effect of levodopa using LDCT that was around 30% improvement. While it lends support to the use of this limit in the MDS diagnostic criteria, an acute effect of less than 30% should be considered acceptable in some patients. Our study highlights a discrepancy in the objective measure of medicine effect on motor symptoms and the patient’s subjective evaluation.